(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
During more than (50) years past, India has achieved considerable social and economic progress. It is also generally assumed that the future progress will be even more rapid and that India will be an important player in the global market. India has only (2.5) percent of global land whereas it has to provide home for one-sixth of world’s population .On examining the past trends of India’s population ,it may be observed that during the latter half of the twentieth century ,about (650) million populations were added to the country ,thus living in a country with a high population density and high growth rate , India in need a transition from high fertility high mortality to a low fertility low mortality and towards stable population situation .India was the first country in Asia which introduced family planning program in the national level in the year (1952) so if we look at fertility transition in comparison to infant mortality rate we get an idea of how India has experienced these transitions will make us understand the overall demographic changes in India .United Nations has projected the total fertility rates below replacement level as (2.1) children per women for India ,so it will be very important to look into details about the mortality – fertility transition and trends of life expectancy at birth of males & females .The declining fertility & mortality & high chance of survival contributions to change in age –composition of population ,India being the second most populous country in the world and having around (1.03) billion of population .The sex ratio in India is more skewed towards in recent decades ,in the decennial census the number of girls per 1000 boys aged (0 – 6) years was (962) in (1981),(945) in (1991) and (927)in (2001) and the discrepancy was more acute in urban area from (959 to 906) between (1981-2001) than the rural area (963-934) ,and that because of the higher mortality rates in female than in male children .Low sex ratios have also been recorded in other Asian countries ,most notably China ,where (847-877) girls were born for every (1000 )boys in (2002) ,India has a higher fertility rates than China. Demographic research over the past decades has confirmed that a preference for sons over daughters remains entrenched in many countries through the world in such setting, religious traditions and social norms coupled with economic discrimination against women & girls conspire to ensure that young boys have greater access to education, health care and even food than do their sisters, such neglect leads to markedly higher rates of illiteracy, malnutrition and poor health among girls. In its first phase of demographic transition, India experienced a steep fall in the mortality rate due to increasing availability and accessibility of improved health care, whereas the fall infertility rate was comparatively less and so the population grew at a rapid speed. In the next phase population continued to grow at a faster rate though the fall in mortality is not steep and fall in fertility continues, until the replacement level of fertility is achieved. Even if the replacement level of fertility is attained, then due to the “momentum” of population growth, it will take a long period to reach at the stable population situation. The reason behind this is that, the large number of people in the reproductive age group will not be so less at the same time. The large number of people in the reproductive age group will not be so less at the same time, particular attention. The first is gender bias - the small number of females compared to males. The number of females per (1000) males is (933) in India compared to a figure of (1,050) for Europe and North America and (1,022) for Sub-Saharan Africa .The second feature is that the fertility rate of Muslim women is considerably higher than that for Hindu women. The latest findings of the National Family Health Survey (NFHS), show that for India as a whole, the Total Fertility Rate (TFR) was (2.8) for Hindus and (3.6) for Muslims. At its most shrill, the higher fertility of Muslim women is blamed on Indian Muslims for obeying the tenets of Islam - and also being driven by their ambition to “outnumber’’ Hindus - in rejecting family planning and embracing polygamy. The aim of this study to show the transitions and the challenges of Indian population through several decades and the prediction of the second population on the earth.